The Emerging Science of Interoception: Sensing, Integrating, Interpreting, and Regulating Signals within the Self. Issue 1 (January 2021) - Chen, Wen G.; Schloesser, Dana; Arensdorf, Angela M.; Simmons, Janine M.; Cui, Changhai; Valentino, Rita; Gnadt, James W.; Nielsen, Lisbeth; Hillaire-Clarke, Coryse St.; Spruance, Victoria; Horowitz, Todd S.; Vallejo, Yolanda F.; et al.
Abstract : Interoception refers to the representation of the internal states of an organism, and includes the processes by which it senses, interprets, integrates, and regulates signals from within itself. This review presents a unified research framework and attempts to offer definitions for key terms to describe the processes involved in interoception. We elaborate on these definitions through illustrative research findings, and provide brief overviews of central aspects of interoception, including the anatomy and function of neural and non-neural pathways, diseases and disorders, manipulations and interventions, and predictive modeling. We conclude with discussions about major research gaps and challenges. Highlights: Interoception refers to the representation of the internal world, and includes the processes by which an organism senses, interprets, integrates, and regulates signals from within itself. The brain communicates with internal organs via the peripheral nervous system and non-neuronal systems. Key components of a unified research framework of interoception include interoceptive signals, interoceptors, ascending and descending pathways, central interpreters, central integrators, central regulators, and interoceptive effectors. In-depth mechanistic studies linking anatomical findings to function are important for defining the roles of the key elements of interoception. Dysfunction of interoception may be an important component of many neurological, psychiatric, and behavioral disorders. Better understanding of the neural basis of interoception may provide therapeutic targets for interoceptive dysfunction and related nervous system disorders.